2003
DOI: 10.1021/cr990372u
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Synthesis and Utilization of Chiral Sulfoxides

Abstract: Recently, Keinan and Nimri reported an interesting antibody-metalloporphyrin that mimics natural oxidation enzyme. 105 On the basis of the catalytic Scheme 14 Scheme 15 Scheme 16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
519
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,133 publications
(523 citation statements)
references
References 354 publications
1
519
0
3
Order By: Relevance
“…2 Chiral sulfur ligands bearing a sulfoxide moiety have been frequently employed as effective catalyst precursors in various enantioselective transformations. [3][4][5][6][7][8] However, only a few S,S-type ligands containing a monosulfoxide have been reported, for example, Skar _ zewski et al 9 reported a chiral sulfoxidethioether ligand (SO-S ligand) based on a rigid cyclopentane backbone (S,S)-1, and high enantioselectivity in asymmetric allylic alkylation reaction was achieved. The authors, however, suggested that it behaved more like an N,S-donating ligand than an S,S-donating ligand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Chiral sulfur ligands bearing a sulfoxide moiety have been frequently employed as effective catalyst precursors in various enantioselective transformations. [3][4][5][6][7][8] However, only a few S,S-type ligands containing a monosulfoxide have been reported, for example, Skar _ zewski et al 9 reported a chiral sulfoxidethioether ligand (SO-S ligand) based on a rigid cyclopentane backbone (S,S)-1, and high enantioselectivity in asymmetric allylic alkylation reaction was achieved. The authors, however, suggested that it behaved more like an N,S-donating ligand than an S,S-donating ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral tert-butanesulfinyl compounds have several advantages: practical and concise synthesis; 3,4,7,8 ortho-lithiation properties; 11 high stereogenic stabilities; 12 effective coordination capability with transition metals and excellent asymmetric inductions. 5,7,8 Recently, we focused our attention on transition-metal-catalyzed asymmetric reactions using chiral sulfoxide (tert-butanesulfinyl) ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36] In the first place, NH 4 NO 3 reacts with NH 4 HSO 4 to produce in situ HNO 3 . Subsequently, auto ionization of HNO 3 generates nitronium ion (NO 2 + ), which is able to convert bromide ion (Br -) to bromonium (Br + ).…”
Section: Resultsmentioning
confidence: 99%
“…Sulfoxides are valuable synthetic intermediates for the synthesis of chemically and biologically significant molecules. [1][2][3] Sulfoxides are also valuable materials in C-C bond-forming 4,5 and molecular rearrangements. [6][7][8] Additionally some of biologically active sulfoxides play an important role as therapeutic agents such as anti-ulcer, [9][10][11] antibacterial, 12 anti-atherosclerotic, 13,14 among others.…”
Section: Introductionmentioning
confidence: 99%
“…1 The vast chemistry of sulfoxides and sulfones makes them useful synthons and intermediates for construction of chemically and biologically significant molecules. 2,3 The chemistry of selenones is of particular interest due to their thermal instability (fragmentation with olefin formation) 4 and their ability to stabilise adjacent anionic centres. 5 Although a plethora of reagents is known for oxidation of sulfides such as potassium permanganate, 6 ortho-iodoxybenzoic acid, 7 periodic acid or molecular bromine, 8 mercury(II) oxide-iodine 9 and benzeneseleninic acid, 10 the oxidation of selenides and tellurides 11 has received only a scant attention.…”
Section: Introductionmentioning
confidence: 99%